Characteristics of cannabinoids composition of Cannabis plants grown in Northern Thailand and its forensic application - Tipparat P. (2014)
The Thai government has recognized the possibility for legitimate cultivation of hemp. Further study of certain cannabinoid characteristics is necessary in establishing criteria for regulation of cannabis cultivation in Thailand. For this purpose, factors affecting characteristics of cannabinoids composition of Thai-grown cannabis were investigated. Plants were cultivated from seeds derived from the previous studies under the same conditions. 372 cannabis samples from landraces, three different trial fields and seized marijuana were collected. 100 g of each sample was dried, ground and quantitatively analyzed for THC, CBD and CBN contents by GC-FID. The results showed that cannabis grown during March-June which had longer vegetative stages and longer photoperiod exposure, had higher cannabinoids contents than those grown in August. The male plants grown in trial fields had the range of THC contents from 0.722% to 0.848% d.w. and average THC/CBD ratio of 1.9. Cannabis in landraces at traditional harvest time of 75 days had a range of THC contents from 0.874% to 1.480% d.w. and an average THC/CBD ratio of 2.6. The THC contents and THC/CBD ratios of cannabis in second generation crops grown in the same growing season were found to be lower than those grown in the first generation, unless fairly high temperatures and a lesser amount of rainfall were present. The average THC content in seized fresh marijuana was 2.068% d.w. while THC/CBD ratios were between 12.6 and 84.09, which is 10-45 times greater than those of similar studied cannabis samples from the previous study. However, most Thai cannabis in landraces and in trial fields giving a low log10 value of THC/CBD ratio at below 1 may be classified as intermediate type, whereas seized marijuana giving a higher log10 value at above 1 could be classified as drug type. Therefore, the expanded information provided by the current study will assist in the development of criteria for regulation of hemp cultivation in Thailand. © 2011.